2010
DOI: 10.1007/s00330-010-1796-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the most infectious lesions in pulmonary tuberculosis by high-resolution multi-detector computed tomography

Abstract: A model to predict smear-positive active PTB on the basis of findings from MDCT may be a useful tool for clinical decisions about isolating patients pending sputum smear results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
(43 reference statements)
3
28
0
2
Order By: Relevance
“…These findings largely agree with recent HRCT studies showing that not only cavitation of s1, s2, and s1+s2 [8] but also consolidation in s1, s2, s1+s2, and s6 [25] and clusters of nodules/mass in s1, s2, and s1+s2 [8] are predictive of culture-positive PTB. This observation is also in accordance with other previous studies [35], [36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings largely agree with recent HRCT studies showing that not only cavitation of s1, s2, and s1+s2 [8] but also consolidation in s1, s2, s1+s2, and s6 [25] and clusters of nodules/mass in s1, s2, and s1+s2 [8] are predictive of culture-positive PTB. This observation is also in accordance with other previous studies [35], [36].…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that HRCT can detect culture-positive PTB and predict the risk of sputum smear-negative and sputum-positive PTB [8][10]. A recent study has reported the cost-effectiveness of using HRCT for detecting culture-positive PTB [10].…”
Section: Introductionmentioning
confidence: 99%
“…Yadav et al 2 reported slightly different findings where the major abnormalities were centrilobular nodules (91%), consolidation (38%), cavity (48%), tree in bud pattern (88%). 2 Yeh et al 7 performed thoracic CT in forty cases of smear-negative TB and reported findings such as centrilobular nodules (51.2%), consolidation (35%), cavity (17.5%), and tree in bud (87.5%). Tree in bud is a sign of endobronchial TB, and a sign of active PTB if it is found in areas of PTB predilection.…”
Section: Discussionmentioning
confidence: 99%
“…Tree in bud is a sign of endobronchial TB, and a sign of active PTB if it is found in areas of PTB predilection. 2,7,9,12 Besides finding abnormalities associated with PTB, thoracic CT scans also find other abnormalities. This study found emphysema in 23 patients (17.7%), bronchiectasis in 16 patients (12.3%), fungal infections in three patients (2.3%) and mass in three patients (2.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation